Методика расчета удаления из воды сероводорода при помощи гидроаэратора - Терновцев, А. В. (Ways to Improve Construction Efficiency, 2012)
The article provides a method of calculating the unit, uses the method of physical degassing of groundwater sulfur hydrogen.